2023
DOI: 10.1002/adfm.202303509
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Bicomponent Adhesives with Instantaneous and Superior Adhesion Performance for Wound Sealing and Healing Applications

Abstract: Surgical adhesives are playing an important role in wound repair and emergency hemostasis in clinical treatment. However, the development of strong bioglue with rapid in situ adhesion, durable adhesiveness, and flexibility in dynamic and moist physiological environments is still challenging. Herein, a new type of biosynthetic protein bioadhesives with superior adhesion performance is reported by developing a protein aldimine condensation strategy. Lysine‐rich recombinant proteins are designed and massively bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Moreover, the TPFe bioadhesive not only had a certain degree of adhesion on the internal organs of rat (heart, liver, spleen, lungs, and kidneys) but also could adhere firmly to the neck and back of rat without falling off for 4 and 5 days, respectively (Figure S6a,c, Supporting Information). Previous studies have shown that rats moved their necks more frequently, including compression, stretching, and twisting, while their backs were in a relatively static state, so the TPFe bioadhesive stuck to their backs for a longer time . When water was poured into the porcine stomach with a leak, the water would flow out of the hole.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the TPFe bioadhesive not only had a certain degree of adhesion on the internal organs of rat (heart, liver, spleen, lungs, and kidneys) but also could adhere firmly to the neck and back of rat without falling off for 4 and 5 days, respectively (Figure S6a,c, Supporting Information). Previous studies have shown that rats moved their necks more frequently, including compression, stretching, and twisting, while their backs were in a relatively static state, so the TPFe bioadhesive stuck to their backs for a longer time . When water was poured into the porcine stomach with a leak, the water would flow out of the hole.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that rats moved their necks more frequently, including compression, stretching, and twisting, while their backs were in a relatively static state, so the TPFe bioadhesive stuck to their backs for a longer time. 40 When water was poured into the porcine stomach with a leak, the water would flow out of the hole. The TPFe bioadhesive was attached to the hole in the porcine stomach, and the porcine stomach was immediately sealed to ensure that the water did not leak out (Figure 3c and Movie S2, Supporting Information).…”
Section: Instant and Strong Adhesion Of The Tpfe Bioadhesivementioning
confidence: 99%